CSF amyloid‐beta, tau, and neurodegenerative and inflammatory biomarkers in cognitively unimpaired late middle‐aged and older adult APOE ε4 homozygotes, heterozygotes, and non‐carriers from the Arizona APOE Cohort. (31st December 2021) - Ghisays, Valentina; Jansen, Willemijn J.; Chen, Yinghua; Protas, Hillary D.; Malek‐Ahmadi, Michael H.; Luo, Ji; Lee, Wendy; Chen, Kewei; Su, Yi; Caselli, Richard J.; Zetterberg, Henrik; Blennow, Kaj; et al.
Abstract: Background: APOE4 gene dose, the number of apolipoprotein E ‐ɛ4 (APOE4) ɛ4 alleles in a person's genotype, is associated with higher Alzheimer's disease (AD) risk and younger median age at dementia onset. We previously found relationships between PET, plasma, and CSF measurements of amyloid‐β (Aβ) pathophysiology in APOE4 gene dose. Here, we characterize the core AD CSF biomarkers (Aβ42/40, pTau181, tTau), the neurodegeneration marker neurofilament light chain (NfL) and the glial biomarkers soluble TREM2 (sTREM2), and glial fibrillary acidic protein (GFAP) measurements in age‐matched 48‐70 year‐old cognitively unimpaired (CU) APOE4 homozygotes (HMs), heterozygotes (HTs) and non‐carriers (NCs) from the Arizona cohort. Method: CSF biomarker measurements were performed at the University of Gothenburg using Lumipulse and ELISA immunoassays. CSF biomarker measurements were characterized and compared using linear‐tend ANOVAs in 12 HMs, 17 HTs, and 20 NCs who were CU, 48‐70 years old and did not differ significantly in their age, sex, or educational level. Result: As expected, CSF Aβ42/40 ratios were inversely associated with APOE4 gene dose (linear trend, HM<HT<NC, p<0.05), and tTau/Aβ42 and pTau181 /Aβ42 ratios were directly associated with APOE4 gene dose (HM>HT>NC p<0.05). Non‐significant trends suggested that CSF sTREM2 and sTREM2/pTau181 measurements were inversely associated with APOE4 gene dose (HM<HT≤NC, (0.05<p≤0.06). We failed to detect significant differences or linear trends in CSF pTau181, tTau, GFAP, or NfL measurements among these small subject groups. Conclusion: APOE4 gene dose is associated with measures of CSF Aβ42/40 and Aβ‐related tau pathophysiology, reflecting higher Aβ plaque burden in CU subjects close to their estimated ages at clinical onset. Additional studies are needed to clarify relationships between different Aβ, tau, neurodegenerative, inflammatory, and other CSF, or blood‐based biomarkers, and APOE4 gene dose in larger subject groups and at other ages.